The First Logistics Zone in Palestine - A Gateway to the World} - Abdelfattah Ala'a Al-Din Dallal; Areen Ahmad Bsharat; Elias Nabegh Braik; Laith Hisham Abu Beih; Nagham Mohammad Zaid (My University, 2021)
logistics zone is a planned area that contains a grouping of activities related to freight distribution. There is a wide array of benefits derived from the accessibility besides the availability of land logistics zones confer, such as reducing the burden on the economic sector, increasing export and import operations, enhancing employment opportunities. This project is about designing a logistics zone, which is intended to be set up on the third phase of Jericho Agro-Industrial Park (JAIP) on 500 dunums of land. It will be connected with Al Karama Bridge via an exclusive trucks highway. The project covers the distribution and analysis of the internal roads, also the design of pavement, besides the concept of the interchange that collect the West Bank trucks, and the determination and design of the number of parking lots needed, and the number of trucks that could be processed. Also, it includes the determination of the number of channels required to serve export and import trucks, and the queue on each of them; to ensure large-scale operations that favor future traffic expectations, besides the management of the traffic movement in terms of the way the trucks will enter and exit the gateways and how the goods will be moved and stored considering the delay due to inspection operations. Furthermore, it includes the selection of an alternative for a proposed layout for the exclusive trucks highway (Al-Salam Highway) to the west of Highway 90, acting as the artery that will connect Palestine with Jordan. A conceptual master plan for the facilities, transportation, and land use was made to guide future growth and development. The importance of this project is that this is the first logistics zone in Palestine, and its presence will stimulate business and commercial traffic, contributing to the recovery of the Palestinian economy. Data was obtained from official agencies in Palestine, in addition to, previous studies about logistics in the region. These include master plans, aerial photographs, the volume of freight traffic that enters and exits the country, and the types of vehicles used to transport the cargo. The amount and volume of goods handled as well as the administrative, procedural, and legal information for the transport operation and how long it takes to end were gathered and analyzed. The design is based on international standards and guidelines such as the AASHTO specifications. Traffic growth analysis is done by using SPSS software, and Queuing Theory for the gateways analysis and design. The maps and aerial photographs were analyzed using GIS software. This project is channeled towards an integrated design that serves the future number of truckloads, besides alternatives for the exclusive highway layout commensurate with the terrain nature of the area